Perhitungan Tingkat Resiko Terhadap Keputusan Investasi Mesin Heidelberg - Dhani, Faricha Amarah; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
KGU is a company operating in the offset printing industry which produces story book series. In the last 6 months, KGU has experienced a decline in productivity and production targets have not been achieved. This happens because Komori engines often experience damage. Frequent downtime causes companies to want to replace machines by considering the company's cash flow. The purpose of this research is to determine the feasibility value of investment. The company will replace the Komori engine, by investing in a Heidelberg engine at a price of Rp. 760,000,0000. Investment analysis uses the NPV, IRR, Payback Period and Profitability Index methods. The results of the analysis used are NPV of IDR 793,678,932 > 0, IRR of 21.72%, payback period for return of investment capital which is 3 years 11 months, profitability index of 2.04> 1. Correlation coefficient value (risk value) 1, 62%. Based on the investment analysis, Heidelberg machines are worth investing in, because investing in these machines can streamline the production process, increase production results and company income